DZIELIMY SIĘ DOŚWIADCZENIEMSignificance of disturbed flow in coronary artery grafts patency - Wasilewski, Jarosław; Kiljański, Tomasz; Głowacki, Jan; Miszalski-Jamka, Karol (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Saphenous vein and radial artery as aortocoronary grafts are often affected by degenerative process with simmilar patency rates. Like internal mammary artery (IMA) in its anatomical position, IMA grafts are resistent against atherosclerosis. Explanation why the IMA conduit is resistant to graft disease but radial artery or saphenous vein as grafts develops intimal hyperplasia and occlusions should be sought in terms of blood flow. This paper attempt to explain this phenomenon based on the graft hydodynamics and the presence of complex secondary flows accompanied by low and oscillatory shear stress. If flow conditions are related to atherogenesis a free saphenous vein coronary conduit anastomosed to subclavian artery may be considered as alternative strategies for aortocoronary grafts in terms of their less tendency of narrowing or occlusion.